American Christianities: a history of dominance and diversity - Brekus, Catherine A. (University of North Carolina Press, 2011)
From the founding of the first colonies until the present, the influence of Christianity, as the dominant faith in American society, has extended far beyond church pews into the wider culture. Yet, at the same time, Christians in the United States have disagreed sharply about the meaning of their shared tradition, and, divided by denominational affiliation, race, and ethnicity, they have taken stances on every side of contested public issues from slavery to women's rights. This volume of twenty-two original essays, contributed by a group of prominent thinkers in American religious studies, provides a sophisticated understanding of both the diversity and the alliances among Christianities in the United States and the influences that have shaped churches and the nation in reciprocal ways. American Christianities explores this paradoxical dynamic of dominance and diversity that are the true marks of a faith too often perceived as homogeneous and monolithic. Contributors: Catherine L. Albanese, University of California, Santa Barbara James B. Bennett, Santa Clara University Edith Blumhofer, Wheaton College Ann Braude, Harvard Divinity School Catherine A. Brekus, University of Chicago Divinity School Kristina Bross, Purdue University Rebecca L. Davis, University of Delaware Curtis J. Evans, University of Chicago Divinity School Tracy Fessenden, Arizona State University Kathleen Flake, Vanderbilt University Divinity School W. Clark Gilpin, University of Chicago Divinity School Stewart M. Hoover, University of Colorado at Boulder Jeanne Halgren Kilde, University of Minnesota David W. Kling, University of Miami Timothy S. Lee, Brite Divinity School, Texas Christian University Dan McKanan, Harvard Divinity School Michael D. McNally, Carleton College Mark A. Noll, University of Notre Dame Jon Pahl, The Lutheran Theological Seminary at Philadelphia Sally M.